Pengaruh Otonomi dan Akuntabilitas Perguruan Tinggi terhadap Kinerja Manajerial - Nurhayati, Isnaeni (TRIKONOMIKA, 2014)
The main objective of this research is investigate the effect of autonomy and accountability on managerial performance . This research uses survey method with verification approach and type of causal research, conducted on 18 universities in Bandung as the unit of analysis, while the unit of observation is a Vice-Chancellor, and Dean. The type of data is primary data collected by a questionnaire research instruments containing ordinal scale for measurement. Validity and reliability tests have also been done on the entire collected questionnaire. Furthermore, data are converted into interval scale, then hypothesis test are done using SPSS 20. This research has shown that (1) Simultaneously, there is a significant effect of autonomy, accountability on managerial performance. (2) Partially only accountabilityt has significant effect on managerial performance. Whereas autonomy does not have significant effect on it.